Construction Handbook Series Project Management, Construction Management and Site Management - Hairuddin Mohammad; Padzil@Fadzil Hassan; Siti Khadijah Yaman (2018)
The particular series are focusing on the realm of construction, where titles are carefully selected in order to give positive impacts on behalf of our Malaysian construction industry. Notwithstanding the ripple effects that might come along the way, the series are believed to benefit peoples from outside the conventional boundary of construction, especially the junior level of students and also the end user.Thus, with regard to this book, we have presented a critical summary of discussions on Construction Project Management. Related definitions, concepts, and other important information were tabulated accordingly to shed lights on some of the notions beneath each terminology. Hopefully, from this little effort that we had embarked on, its knowledge will find a restful place where subsequent enrichment continues.